Жизнь птиц у нас дома - Беме Лев Борисович (Библиотечная серия, 1986)
Экземпляры: ЦБ/19/21/22/23/26/27/31 (20250116) / Инвентарный номер: 15333 / Цена: 1.10 / Сис.шифр: 46.87 / Авт.знак: Б 45 / ГРНТИ: 68.39.37 / ББК: 46.87